Impact of foreign direct investment on research and development, and income inequality - Mahamad Zakaria, Muhammad Farhan (2015)
This dissertation consists of two independent essays, both of which are empirical assessments of economic impacts of foreign direct investment. The first essay investigates the impact of foreign direct investment (FDI) inflows on R&D activities in 48 developing countries, covering the 1996-2013 period. Based on the system Generalized Method of Moment (GMM) approach, our panel data analysis suggests that FDI inflows tend to discourage R&D activities in the host countries. This finding is consistent with the view that competition introduced by FDI encourages local firms to opt for a cheaper way for technology upgrading via imitation. Moreover, there is evidence that R&D activities in developing countries has benefited from imported technologies and stronger legal protection for R&D activities. The second essay tests the impact of FDI on income inequality in ASEAN-5 countries,namely Indonesia, Malaysia, the Philippines, Singapore, and Thailand. Using the quantile regression methodology and a data set for the 1980-2013 period, the findings reveal that FDI inflows into Indonesia, Malaysia, Singapore and Thailand appear to widen income inequality. In the Philippines, FDI is found to have a reducing effect on income inequality. These findings suggest that countries with different economic environments tend to derive different benefits and costs from FDI inflows.